1993
DOI: 10.1096/fasebj.7.1.7678559
|View full text |Cite
|
Sign up to set email alerts
|

Mis-splicing yields circular RNA molecules.

Abstract: We previously identified novel human ets-1 transcripts in which the normal order of exons is inverted, and demonstrated that although the order of exons is different than in the genomic DNA, splicing of these exons out of order occurs in pairs using genuine splice sites (1). Here we determine the structure of these novel transcripts, showing that they correspond to circular RNA molecules containing only exons in genomic order. These transcripts are stable molecules, localized in the cytoplasmic component of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
711
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,004 publications
(747 citation statements)
references
References 17 publications
8
711
0
3
Order By: Relevance
“…Both Group I introns (found in eukaryotes and bacteria) and bulge-helixbulge-derived introns (found in archaea) can be circularized after excision from precursor tRNA and rRNA (18,21,22,35,36). In addition, in rare cases aberrant mRNA processing in eukaryotes can generate circular mRNA fragments (37)(38)(39)(40). The previously described circular RNAs are not known to function directly in cellular processes, making the possibility that circular box C͞D RNAs guide RNA modification in archaea even more provocative.…”
Section: Resultsmentioning
confidence: 99%
“…Both Group I introns (found in eukaryotes and bacteria) and bulge-helixbulge-derived introns (found in archaea) can be circularized after excision from precursor tRNA and rRNA (18,21,22,35,36). In addition, in rare cases aberrant mRNA processing in eukaryotes can generate circular mRNA fragments (37)(38)(39)(40). The previously described circular RNAs are not known to function directly in cellular processes, making the possibility that circular box C͞D RNAs guide RNA modification in archaea even more provocative.…”
Section: Resultsmentioning
confidence: 99%
“…Only a small number of circRNAs in different organisms have been identified, and they were generally disregarded as the results of mis-splicing and as by-products of pre-mRNA processing. [3][4][5][6] However, recent advances using biochemical enrichment strategies and novel bioinformatics approaches coupled with deep sequencing have allowed comprehensive investigation of circRNAs. [7][8][9][10] Specifically, a large number of circRNAs have been successfully identified in various cell lines and across different species.…”
Section: Introductionmentioning
confidence: 99%
“…1 Additional studies reported further new examples of circRNAs over the years, [2][3][4][5][6][7][8][9] yet the extent of the prevalence of the circularization phenomenon was not clear, as the available examples remained limited. The advent of high-throughput sequencing revealed that circRNAs are a large class of abundant RNAs with complex developmental-and cellspecific expression patterns.…”
Section: Introductionmentioning
confidence: 99%